2008
DOI: 10.1007/s10198-008-0136-z
|View full text |Cite
|
Sign up to set email alerts
|

Material versus social deprivation and health: a case study of an urban area

Abstract: Socioeconomic factors are one of the main determinants of health inequalities. However, which component of socioeconomic status affects health most and how that relationship should be measured remains an open question. The aim of this study was to compare material and social deprivation indexes in order to determine which better explains health inequalities within an urban area. Following a review of the literature on small area deprivation indexes, a case study of the Italian city Genoa is presented. The city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
(31 reference statements)
0
24
0
6
Order By: Relevance
“…This finding contradicts the notion that deprivation, being a function of shortage in financial capital, should be a more proximate indicator of risk than income. 24,32 Disparities in findings might be a result of the lack of data for measuring financial difficulty in the LoveLife data set, an important limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding contradicts the notion that deprivation, being a function of shortage in financial capital, should be a more proximate indicator of risk than income. 24,32 Disparities in findings might be a result of the lack of data for measuring financial difficulty in the LoveLife data set, an important limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on high-income countries have found a strong association between material deprivation and health behavior. 17,[21][22][23][24] However, there is no consensus to date on what constitutes material deprivation and the research output on such relationships on low-income countries is relatively limited. Moreover, Burns and Snow 19 argue that commonly used constructs of deprivation in high-income countries do not adequately represent the conditions and realities of low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…La deprivazione, essendo uno "stato di svantaggio" degli individui che vivono in un certo territorio, può essere analizzata sotto un duplice aspetto: la deprivazione materiale comporta la mancanza di beni, servizi, risorse, comodità normalmente godute o almeno largamente accettate come beni primari (Testi e Ivaldi, 2009). La deprivazione sociale, d'altro canto, sottende ad una non partecipazione nei ruoli, relazioni, usi, funzioni, diritti e responsabilità implicati dall'essere membro di una data società o di un suo sotto gruppo (Townsend, 1987;Townsend et al, 1988).…”
Section: Deprivazione Materiale E Socialeunclassified
“…B. Frankreich [ 34 ] , Italien [ 35 ] , Schweden [ 36 ] , Spanien [ 37 ] , der Tschechischen Republik [ 38 ] oder Ungarn [ 39 ] . Auch in Deutschland gibt es entsprechende Ansätze zur Erfassung regionaler Deprivation und zu ihrer Analyse in gesundheitlichen Fragestellungen, wie z.…”
Section: Deprivationsindizes In Anderen Staaten Der Europäischen Unionunclassified